Pelaksanaan Verifikasi Partai Politik Calon Peserta Pemilu Tahun 2014 di KPU Kota Padang - Oxana Putra, Erix (Greenation Publisher & Yayasan Global Resarch National, 2023)
Abstract: The purpose of this research is to reveal the problems faced by the General Election Commission (KPU) of Padang City during the verification process. The results of the study indicate that there are problems experienced by the Padang City Election Commission when verifying political parties as candidates for election contestants. First, the difficulty in applying the political party information system (Sipol) during administrative verification. With the reason that the decline in party data in Sipol is difficult to access, the network is disrupted and the data is inaccurate. Second, the difficulty in verifying factual data. Where fictitious data was found, addresses submitted by political parties were incomplete, and multiple members were in two different parties. Abstrak: Tujuan penelitian ini ialah untuk mengungkapkan permasalahan yang dihadapi oleh Komisi Pemilihan Umun (KPU) Kota Padang selama proses verifikasi berlangsung. Hasil penelitian menunjukkan bahwa terdapat permasalahan yang dialami KPU Kota Padang saat melaksanakan verifikasi partai politik calon peserta pemilu. Pertama, kesulitan dalam mengaplikasikan Sistem informasi partai politik (Sipol) pada saat verifikasi administrasi. Dengan alasan data keanggotaan partai yang ada di Sipol sulit diakses, jaringan terganggu dan data yang ada kurang akurat. Kedua, kesulitan dalam memverifikasi data faktual. Dimana ditemukan data yang fiktif, alamat yang diserahkan partai politik kurang lengkap dan anggota ganda di dua partai yang berbeda.